Stress distribution in knee Implant: A FEA study. (2022) - Jackson Irudhayam, S.; Antony Prabu, D.; Jayakumar, K.S.; Hariram, V.; Sankaralingam, T.
Abstract: The line-of-life of knee implant is dependent on design and material of the component. This work benefits to discover the outcome of femoral design and feasible implant biomaterial. The role of implant design plays a dynamic part to promise transplant steadiness. Femoral segment design entrenched for knee readapt and geometrical details are homogeneous. Modeling's of implant carry through by solid works and investigation done by Ansys tool to find stress dispensation in knee implant. As materials constitute extensive impingement on stress distribution, PEEK material was considered in this study. As a result Stress heedfulness was presumed by this work. Stress distribution between femoral and tibial part contemplated by CAE software. Design and material of the implant plays vital role in order to moderate the stress level in implant part. Hence this work expresses the impact created by change of knee implant design and implant biomaterial in transplantation.